Risk for endoparasites among production stages of female goats with notes on sustainable parasite control for smallholder flocks - Paul, Bura Thlama; Faez Firdaus Abdullah Jesse,; Juriah Kamaludeen,; Yonis Ahmed Jimale,; Ali Saidu,; Jajere, Saleh Mohammed; Mohd Azmi Mohd-Lila, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The risk of parasitism in different groups of small ruminants depends on intrinsic, environmental, and management factors. Although there are different views regarding the sex-related risk of endoparasites in small ruminants, females are undoubtedly the most affected group in the flock. Moreover, whether the greater sex-specific risk of parasitic infection observed in female goats in field situations is associated with their production or other intrinsic factors is still under scrutiny. In this paper, cross-sectional epidemiological data collected from selected small ruminant flocks were analysed to determine the distribution, risk, and burden of endoparasites in young, nonpregnant, pregnant, and lactating female goats. There was a higher incidence of gastrointestinal parasites (88.4%, 95%CI= 83.01- 92.19) than blood protozoa (54.0%, 95%CI= 46.85-60.92), with a significant difference among the groups. A higher risk of gastrointestinal parasites was observed in lactating (OR = 46.667, P = 0.001) and pregnant (OR = 9.167, P = 0.003) groups. A greater risk of blood protozoan infection was also observed in the pregnant (OR = 5.971, P = 0.0104) and lactating (OR = 3.600, P = 0.0528) groups. A significant increase in the mean faecal egg count of the lactating (2.72 ± 0.76) and pregnant (2.34 ± 0.97) groups (P < 0.05) was accompanied by a significantly lower mean PCV in the lactating group (23.48 ± 4.838) than the kids (29.44 ± 6.13), or nonpregnant (27.80 ± 5.525) groups (P < 0.05). Thus, the pregnant and lactating female goats may experience a greater exposure risk and burden of endoparasites. Therefore, female goats may be selectively targeted for implementing nutritional management, controlled grazing, and selective anthelmintic treatment during pregnancy and lactation to save cost and minimise excessive use of anthelmintic.